Radiation Response of Human Leukemia/Lymphoma Cells was Improved by 7-Geranyloxycoumarin - Ramin Bagheri; Fatemeh B. Rassouli; Hamid Gholamhosseinian; Keyhan Ebrahimi; Shakiba Mahdavi; Sajad Goudarzi; Mehrdad Iranshahi; Houshang Rafatpanah; Mohammad Reza Keramati (SAGE Publishing, 2022)
Objectives Adult T-cell leukemia/lymphoma (ATLL) is a blood neoplasm with specific geographic distribution. Although radiotherapy is a palliative treatment that provides long-term local control, single use of radiation leads to complications for patients. To introduce a novel multimodal approach against ATLL, we investigated combinatorial effects of 7-geranyloxycoumarin and radiation in vitro. Methods Viability of MT-2 cells was determined by resazurin assay upon administration of 7-geranyloxycoumarin alone and followed by radiation. Then, apoptosis was detected by annexin V and propidium iodide, and the expression of candidate genes was analyzed by qPCR. Results Findings revealed significant (P<.0001) improvement in radiation effects upon 7-geranyloxycoumarin pretreatment, most notably when cells were pretreated with 5 µg/ml 7-geranyloxycoumarin for 96 h, exposed to 6 Gy radiation and recovered for 48 h. These results were confirmed by flow cytometry, as the percentage of early and late apoptotic cells was increased after combinatorial treatment. In addition, significant (P< .0001) changes in CD44 , c-MYC , cFLIPL , BMI-1 , NF-κB ( Rel A ), and P53 expression was induced by 7-geranyloxycoumarin and radiation. Conclusions Current research indicated, for the first time, that combinatorial use of 7-geranyloxycoumarin and ionizing radiation could be considered as an effective therapeutic modality for ATLL.